Cryptanalysis and improvement of an encryption scheme that uses elliptic curves over finite fields - Zia, Malik; Ali, Rashid (Kuwait Journal of Science, 2021)
In this paper, we cryptanalyzed a recently proposed encryption scheme that uses elliptic curve over a finite field. The security of proposed scheme depends upon elliptic curve discrete logarithm problem. Two secret keys are used to increase the security strength of proposed scheme as compared to traditionally used one secret key based schemes. In proposed scheme, if an adversary gets one secret key then still he unable to get the contents of original message without the second secret key. Our analysis shows that the proposed scheme is not secure and unable to provide the basic security requirements of encryption scheme. Due to our successful cryptanalysis, anyone can able to get the contents of original message from the public parameters, without any secret key. The attempt of improving the security of proposed cryptosystem by increasing the number of secret keys cannot provide the enhanced security.